Recent development in the application of immobilized oxidative enzymes for bioremediation of hazardous micropollutants – A review. (January 2020) - Shakerian, Farid; Zhao, Jing; Li, Shao-Ping
Abstract: During the past several years, abundant progresses has been made in the development of immobilized oxidative enzymes with focus on finding new support materials, improving the immobilization methods and their applications. Nowadays, immobilized oxidative enzymes are broadly accepted as a green way to face the challenge of high amounts of micropollutants in nature. Among all oxidative enzymes, laccases and horseradish peroxidase were used frequently in recent years as they are general oxidative enzymes with ability to oxidize various types of compounds. Immobilized laccase or horseradish peroxidase are showed better stability, and reusability as well as easy separation from reaction mixture that make them more favorable and economic in compared to free enzymes. However, additional improvements are still essential such as: development of the new materials for immobilization with higher capacity, easy preparation, and cheaper price. Moreover, immobilization methods are still need improving to become more efficient and avoid enzyme wasting during immobilization and enzyme leakage through working cycles. Highlights: Current status of immobilized oxidative enzymes for micropollutants bioremediation. Immobilized enzymes vs. free enzymes for micropollutants degradation. Micropollutants bioremediation by immobilized enzymes from analytical points of view.